The impact and influence of change on a residential aged care community: an action research study - Horner, Barbara Joan (Curtin University, 2005)
This study was an investigation of the complexities and challenges of change in a community-based aged care facility in Western Australia, to reveal the impact and influence of change on the community. It explored the impact of change on both the residents and the senior management team, as leaders of the organisation, and explored how change influenced the redevelopment process and future of the organisation. There is considerable literature on organisational change including the impact of change on the structure, function, process, workforce and leaders of the organisation. There is, however, little literature on organisational change within aged care communities, particularly with an emphasis on the complexities and challenges associated with change within an organisation that is both a business and a home for its residents. The study took the form of a participative action research study, occurring predominantly over two years (2002-2003) with some continuation into a third year (2004). The study had three phases and included two action research cycles and a critical reference group (CRG), comprising the senior management team (SMT) and researcher. It adopted a broadly qualitative methodology, using data from participatory observation and semi-structured interview; however, it did include quantitative and qualitative data from two 'quality of service' surveys for independent living residents and a staff satisfaction survey. The finding of this study are presented as a narrative account of the experiences of the participants. The study reveals that change associated with the redevelopment impacted on residents' wellbeing, described by them as quality of life.The redevelopment process and associated change also emphasised the importance of communication and explanation with residents to understand elements of quality of life and to monitor and manage the impact of change. The findings of the study highlight the challenge faced by community-based aged care communities classified by government, the industry and the wider community as primarily not-for-profit, to balance financial accountability and social conscience. The perception of benevolence influenced the attitudes of residents and staff and made business accountability more difficult to explain and realise. The study reveals that change also impacted on the structure and function of the organisation as it built its capacity for change. It reshaped the relationship between the Board and senior management team (SMT), which was reported as an improvement in communication, work relations and leadership effectiveness. The development of the leadership team, being the senior management team, was influenced by change and the change process enabled this team to become a competent, confident, cohesive senior team, with a preferred leadership style. A further finding was the realisation of the value and appropriateness of the action research process. It provided tools and processes that were used to plan, act, analyse and reflect on the many aspects of organisational change and enabled the organisation, principally the SMT, to reflect on the impact and influence of change. The research process supported their development as leaders as well as the development of the team. The process of planning, collecting data, analysing data, reflection and action provided a structure and process that they continued to use in their management practices, as new situations continued to arise with the redevelopment process.